Tales of the City - Maupin, Armistead (London Black Swan, 1978)
A naive young secretary forsakes Cleveland for San Francisco, tumbling headlong into a brave new world of laundromat Lotharios, cut throat debutantes and jockey shorts dance contests.
Keywords: California--San Francisco -- City and town life -- Tolliver, Michael (Fictitious character)